"I'm Not Going to Be, Like, for the AP": English Language Learners' Limited Access to Advanced College-Preparatory Courses in High School. (October 2014) - Kanno, Yasuko; Kangas, Sara E. N.
Advancement to postsecondary education for English language learners (ELLs) can be seriously constrained by a lack of academic preparation during high school. Currently, ELLs lag behind their non-ELL peers in their level of access to advanced college-preparatory courses. Through a qualitative case study of ELL education at a large public high school, we examine the educational practices that result in ELLs' restricted curricular choices. The findings expose the way in which ELLs' chances for rigorous academic preparation are systematically reduced and point to the importance of providing ELLs with high-level academic curriculum while also supplying linguistic scaffolding that makes such learning possible.